2020
DOI: 10.12688/wellcomeopenres.15474.2
|View full text |Cite
|
Sign up to set email alerts
|

Punishing the individual or the group for norm violation

Abstract: Background: It has recently been proposed that a key motivation for joining groups is the protection from consequences of negative behaviours, such as norm violations. Here we empirically test this claim by investigating whether cooperative decisions and the punishment of associated fairness-based norm violations are different in individuals vs. collectives in economic games. Methods: In the ultimatum game, participants made or received offers that they could reject at a cost to their outcome, a form of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
(3 reference statements)
0
11
2
Order By: Relevance
“…We found a robust reduction in proposed punishment across instances of intended and accidental harm when perpetrators acted as part of a group rather than lone agents. The contrast between these results and previous studies (Feldman & Rosen, 1978;El Zein et al, 2020) may be attributed to the more representative range of clearly and more strongly harmful causations (i.e., death) represented in our materials. That no diffusion of punishment was observed for attempted harm suggests that diffusion of punishment depends on discounting principle in causal attribution of harmful outcomes rather than intentions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found a robust reduction in proposed punishment across instances of intended and accidental harm when perpetrators acted as part of a group rather than lone agents. The contrast between these results and previous studies (Feldman & Rosen, 1978;El Zein et al, 2020) may be attributed to the more representative range of clearly and more strongly harmful causations (i.e., death) represented in our materials. That no diffusion of punishment was observed for attempted harm suggests that diffusion of punishment depends on discounting principle in causal attribution of harmful outcomes rather than intentions.…”
Section: Discussioncontrasting
confidence: 99%
“…However, a follow-up experiment on hypothetical robberies failed to find corroborating evidence, a result ascribed to the small sample size (Feldman & Rosen, 1978). More recently, El Zein et al (2020) investigated second-party punishment in fairness-based group games but found no difference between proposed punishment for lone fairness violators compared with collective ones (El Zein et al, 2020). Another study of the punishment of cheaters showed that group actors were considered less dishonest than individual actors, but differences in judgments of deserved punishment were only marginally significant (p = .08; Vainapel et al, 2019).…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Responsibility context [1,2,3,4] as for the behavioural analyses: 1= Private, 2= Dyadic, 3= Group, 4= Forced. Please note that negative parameter estimates indicate higher activity for more responsibility.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps more alarmingly, collective context allows us to disavow ourselves of regret 7 as well as offload blame onto others 8 when outcomes are not good. Correspondingly, people find it harder to punish groups (vs individuals) who have violated a social norm 8 . In 2003, when weapons of mass destruction were not found in Iraq, or indeed over the following years, intelligence agencies whose reports had justified a catastrophic invasion of Iraq defended themselves by invoking that "everyone had agreed at the time".…”
Section: Introductionmentioning
confidence: 99%